Diagnosing adult and pediatric extrapulmonary tuberculosis by MPT64 antigen detection with immunohistochemistry and immunocytochemistry using reproduced polyclonal antibodies - Ole Magnus Bjørgaas Helle; Mala Kanthali; Sheeba Ishtiaq; Atiqa Ambreen; Manju Raj Purohit; Tehmina Mustafa (Wiley, 2024)
Abstract Diagnosing extrapulmonary tuberculosis (EPTB) is challenging. Immunohistochemistry or immunocytochemistry has been used to diagnose tuberculosis (TB) by detection of MPT64 antigen from various extrapulmonary specimens and has shown good diagnostic performance in our previous studies. The test can distinguish between disease caused by Mycobacterium tuberculosis (Mtb) complex and nontuberculous mycobacteria and can be applied on formalin‐fixed paraffin‐embedded tissue. As the antibodies previously used were in limited supply, a new batch of polyclonal antibodies was developed for scale‐up and evaluated for the first time in this study. Our aim was to assess the diagnostic accuracy of the MPT64 test with reproduced antibodies in the high burden settings of Pakistan and India. Patients were enrolled prospectively. Samples from suspected sites of infection were collected and subjected to histopathologic and/or cytologic evaluation, routine TB diagnostics, GeneXpert MTB/RIF (Xpert), and the MPT64 antigen detection test. Patients were followed until the end of treatment. Based on a composite reference standard (CRS), 556 patients were categorized as TB cases and 175 as non‐TB cases. The MPT64 test performed well on biopsies with a sensitivity and specificity of 94% and 75%, respectively, against a CRS. For cytology samples, the sensitivity was low (36%), whereas the specificity was 81%. Overall, the MPT64 test showed higher sensitivity (73%) than Xpert (38%) and Mtb culture (33%). The test performed equally well in adults and children. We found an additive diagnostic value of the MPT64 test in conjunction with histology and molecular tests, increasing the yield for EPTB. In conclusion, immunochemical staining with MPT64 antibodies improves the diagnosis of EPTB in high burden settings and could be a valuable addition to routine diagnostics.